(untitled) (Siddhajyoti Interdisciplinary Journal, 2020)
This paper explores on how Tamang children achieve elementary education along with their socioeconomic conditions. This study tries to assess the impact of living condition, home and surrounding environment, parental education, and economic condition of the family on elementary education of Tamang children of Dhankuta district, aged 6-14 of. Data were collected from 15 households, purposively selected, through interview and observation, and the thematic analysis was done employing qualitative research design. It was found that, of the total 18 children,27.27% were non-enrolled, 24.14% drop-outs while 48.56% were continuing formal education. It was also found that the economic factors (poverty), family size, and home condition were the major struggle of the Tamang children in achieving elementary education. To combat with these issues income generation and poverty alleviation programs should be properly implemented; more job opportunities and shelters for the shelterless families are to be provided at low and affordable prices; and teachers and school authorities should make the parents aware about the importance of sending children regularly to school.